PROVISION OF COMMUNICATIONS AND INFORMATION SECURITY IN CENTRIC NETWORK TROOPS CONTROL AND VARIOUS SCENARIOS OF ATTACKING TELECOMMUNICATIONS NETWORK - Yu. A. Semashko; V. M. Kalinin; v. n. Sheptura (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Place and role of telecommunications network as the basis of creating unique informative space in conducting centric network warfare is determined. Aspect of vulnerability of telecommunications networks to provide communications security and information protection is analyzed. The most scenarios of attacking network and their consequences are considered. The main requirements to communications security and information protection are formulated. General solution of the problem of creating stable to the attacks telecommunications network is suggested.